Inflammatory side effects of BRAF and MEK inhibitors. Issue 5 (October 2019) - Mackin, Anna G.; Pecen, Paula E.; Dinsmore, Amanda L.; Patnaik, Jennifer L.; Gonzalez, Rene; Robinson, William A.; Palestine, Alan G.
Abstract : The aim of this study was to describe inflammatory side effects in patients treated with BRAF and MEK inhibitors at a single tertiary care institution. This was a retrospective chart review of patients prescribed single-agent or combination BRAF and MEK inhibitors from January 2010 until May 2015. The primary outcome was the presence of inflammatory side effects. Among 124 patients, 56.4% were male, the median age was 59 years, and most (91.1%) were treated for metastatic melanoma. Most patients (74.2%) developed inflammatory side effects, some with multiple occurrences, for a total of 211 occurrences. The overall prevalence of inflammatory side effects did not differ across therapies. In a subanalysis, patients treated with both single-agent and combination therapies were more likely to experience an inflammatory side effect on single-agent therapy ( P = 0.0126 for BRAF inhibitor, P = 0.0833 for MEK inhibitor). The most common inflammatory side effects for the entire cohort included arthralgias/myalgias (32.9%), nonacneiform rash (28.0%), pyrexia (25.5%), and erythema nodosum (11.2%), although side effects differed across the class of therapy. Corticosteroids were initiated in 73 side effect instances among 47 patients. Drug interruption or dose reduction was reported in 78 side effect instances in 50 patients. Fifteen side effect instances led to treatment termination. There is a high prevalence of inflammatory side effects encompassing all organ systems in patients treated with BRAF and MEK inhibitors. There is no significant difference in the prevalence of inflammatory side effects in patients treated with single-agent versus combination therapies, however, side effect profile differs across agents.